INFLUENCE OF HEALTH INSURANCE ON CLINICAL DECISION MAKING AMONG KENYAN DOCTORS - YULU, ELIJAH (KABARAK UNIVERSITY, 2019)
The vast majority of Kenyans lack any form of health insurance. Thus, they find it difficult to raise money for health expenditure. As a result, studies elsewhere have shown an obvious disadvantage to uninsured individuals in terms of health care accorded to them when compared to patients with insurance. However, there is a scarcity of research in Kenya to evaluate whether lack of insurance affects the kind of health care they receive. The main objective of this study was to examine the presence or absence of change in clinical decisions among Kenyan doctors depending on the health insurance status of a patient. This research study used a cross-sectional survey which used an online self-administered questionnaire. The questionnaire sought to find out if respondents had changed their clinical decisions on the basis of the health insurance status of their patients. Further, the tool asked respondents if they thought the decision change impacted the patients’ health care negatively or positively. Analysis of the responses involved categorical independent and dependent variables. Chi-square test was used to measure significance for a p-value of/or less than 0.05 using SPSS 19 software. The completed responses were 183 (20 % of total surveyed), 25 questionnaires were incomplete and thus excluded, leaving 158 which were analyzed. Of the respondents’ data analyzed, 84% reported that they had changed their clinical decisions on basis of the health insurance status of the patients. There was a significant difference in the clinical decision by the doctors between uninsured patients and those insured (71% decision change for uninsured vs. 93% for the insured; p<0.05). Decision change was perceived to be harmful with an average score of -0.24. Likely harm was higher in uninsured (-0.48) compared to insured (-0.34, p > 0.05). Respondents in private practice were more likely to change decisions on basis of health insurance status compared to those in public practice (94% vs. 17%; p<0.05). The overall effect was likely to be beneficial to those working in private (average score =+0.2) but tending to harm (average score = -0.2) in those working for public hospitals. Health insurance did not influence clinical decisions among respondents in emergency conditions (p>0.05). Findings of this study revealed that clinical decision making of Kenyan doctors is influenced by health insurance. Insured patients were likely to receive better care than the uninsured. A recommendation is made to the government bodies to formulate policies that ensure that healthcare is universally available regardless of insurance status. The government can consider formulating a policy to enhance universal health insurance inclusion.
FULL TEXT
Keywords: Health insurance, Emergency medical care, Private practitioners, Public health facilities, Clinical decisions